Mutation at G103 of MtbFtsZ Altered their Sensitivity to Coumarins - Sridevi, Duggirala; Sudhakar, Karpagam U.; Ananthathatmula, Ragamanvitha; Nankar, Rakesh P.; Doble, Mukesh (Frontiers in Microbiology, 2017)
Coumarins are natural polyphenol lactones comprising of fused rings of benzene and α-pyrone. The current study demonstrates the inhibitory effect of coumarins with various substitutions on Mycobacterium smegmatis mc2155. We also demonstrate the effect of pomegranate (Punica granatum) extract containing ellagic acid, on M. smegmatis as well as their affect on MtbFtsZ (FtsZ from Mycobacterium tuberculosis). The ellagic acid extracts from pomegranate peels inhibit mycobacteria with a MIC of 25 µM and 0.3 to 3.5 mg / mL, respectively, but failed to inhibit the polymerization of MtbFtsZ. However the coumarins were shown to inhibit the polymerization and GTPase activity of the protein as well as have an inhibitory affect on M. smegmatismc2155. Docking of the most active coumarin (7-Dimethyl-4-methyl coumarin with MIC of 38.7 µM) to the GTP binding site suggests that it interacted with the G103 residue. Based on the docking results two mutants of varying activity (G103S and G103A) were constructed to elucidate the interaction of MtbFtsZ and coumarins. Mutation of G103 with Serine (a bulky group) results in an inactive mutant and substitution with alanine produces a variant that retains most of the activity of the wild type. There is a disruption of the protofilament formation of the MtbFtsZ upon interaction with coumarins as demonstrated by TEM. The coumarins increase the length of Mycobacteria five times and MtbFtsZ localization is disturbed. The mutant proteins altered the GTPase and polymerization activity of coumarins as compared to wild type protein. The results here support that coumarins inhibit proliferation of Mycobacteria by targeting the assembly of MtbFtsZ and provide the possible binding site of coumarins on MtbFtsZ. This study may aid in the design of natural products as anti-mycobacterial agents. The currently reported GTP analogues for FtsZ are toxic to the human cell lines; natural coumarins targeting the GTP binding site of MtbFtsZ may hold promise as an important drug lead for tuberculosis treatment.